Patterns of morphological integration in marine modular organisms: supra-module organization in branching octocoral colonies - Sánchez, Juan Armando; Lasker, Howard R (Proceedings of the Royal Society B : Biological Sciences, 2003)
Despite the relative simplicity of their modular growth, marine invertebrates such as arborescent gorgonian octocorals (Octocorallia: Cnidaria) generate complex colonial forms. Colony form in these taxa is a consequence of modular (polyp) replication, and if there is a tight integration among modular and supramodular traits (e.g. polyp aperture, inter-polyp spacing, branch thickness, internode and branch length), then changes at the module level may lead to changes in colony architecture. Alternatively, different groups of traits may evolve semi-independently (or conditionally independent). To examine the patterns of integration among morphological traits in Caribbean octocorals, we compared five morphological traits across 21 species, correcting for the effects of phylogenetic relationships among the taxa. Graphical modelling and phylogenetic independence contrasts among the five morphological characters indicate two groups of integrated traits based on whether they were polyp- or colony-level traits. Although all characters exhibited bivariate associations, multivariate analyses (partial correlation coefficients) showed the strongest integration among the colony-level characters (internode distance and branch length). It is a quantitative demonstration that branching characters within the octocorals studied are independent of characters of the polyps. Despite the universally recognized modularity of octocorals at the level of polyps, branching during colony development may represent an emergent level of integration and modularity.